2021
DOI: 10.1089/mdr.2019.0419
|View full text |Cite
|
Sign up to set email alerts
|

Spread of OXA-48 and NDM-1-Producing Klebsiella pneumoniae ST48 and ST101 in Chicken Meat in Western Algeria

Abstract: We investigated the prevalence of carbapenemase-producing Enterobacteriaceae (CPE) in chicken meat in Western Algeria in 2017. Results: From February to July 2017, samples of chicken meat from three poultry farms in Western Algeria were screened for the presence of CPE. Strains were characterized with regard to antibiotic resistance, blactamase content, Plasmid-mediated quinolone resistance, sulfonamide resistance genes, clonality (repetitive sequence-based profiles and multilocus sequence typing) and virulenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 52 publications
(86 reference statements)
1
18
2
Order By: Relevance
“…On the other hand, WGS analysis of Klebsiella species showed that K. pneumoniae had a novel ST, that was closely matched to ST1224, and ST48 alleles. In earlier studies, K. pneumoniae ST1224 was isolated from neonates ( Chen et al, 2019 ), while K. pneumoniae ST48 was reported in chicken meat in Western Algeria, one of the Middle East region ( Chaalal et al, 2021 ) indicating that these STs are not host specific and could be easily transmitted to humans from food animals and their products.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, WGS analysis of Klebsiella species showed that K. pneumoniae had a novel ST, that was closely matched to ST1224, and ST48 alleles. In earlier studies, K. pneumoniae ST1224 was isolated from neonates ( Chen et al, 2019 ), while K. pneumoniae ST48 was reported in chicken meat in Western Algeria, one of the Middle East region ( Chaalal et al, 2021 ) indicating that these STs are not host specific and could be easily transmitted to humans from food animals and their products.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to reports of invasive infections, contamination of food animals or food products with MDR K. pneumoniae has been reported ( Davis and Price, 2016 ; Wu et al, 2016 ; Projahn et al, 2019 ). Recently, the presence of NDM-1 carbapenemase-producing ST101 K. pneumoniae has been reported in chicken meat in Algeria ( Chaalal et al, 2020 ). Likewise, other high-risk MDR clones, such as ST11 and ST258, have been detected in animals in China ( Yang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although ARGs existed long before antibiotics became discovered and put into a wide use (Hall and Barlow, 2004;Allen et al, 2010), our irresponsible use of antibiotics in animal husbandry, overuse of antibiotics in health care, improper treatment of wastewaters and poor sanitation in low and middle income countries has led to wide spread of resistant bacteria across the globe (Prestinaci et al, 2015;Holmes et al, 2016;Ma et al, 2020). To date, the most worrisome global spread of ARGs is the plasmid-mediated spread of carbapenemases (KPC, NDM, VIM, OXA-48, and OXA-51); colistin-resistance genes (mcr) in Enterobacteriaceae, Acinetobacter baumannii, and Pseudomonas aeruginosa; vancomycin resistance gene (vanA) in Enterococci and Staphylococcus aureus; and methicillin resistance gene (mecA) in S. aureus (de Niederhausern et al, 2011;Poirel et al, 2014;Lerner et al, 2015;Wang R. et al, 2018;Chaalal et al, 2020;Hishinuma et al, 2020;Snitser et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the most worrisome global spread of ARGs is the plasmid-mediated spread of carbapenemases (KPC, NDM, VIM, OXA-48, and OXA-51); colistin-resistance genes ( mcr ) in Enterobacteriaceae , Acinetobacter baumannii , and Pseudomonas aeruginosa ; vancomycin resistance gene ( vanA ) in Enterococci and Staphylococcus aureus ; and methicillin resistance gene ( mecA ) in S . aureus ( de Niederhausern et al, 2011 ; Poirel et al, 2014 ; Lerner et al, 2015 ; Wang R. et al, 2018 ; Chaalal et al, 2020 ; Hishinuma et al, 2020 ; Snitser et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%